The Speed of Human and Task Integration in Mergers and Acquisitions Human Integration as Basis for Task Integration - Proft, Carolin. (BestMasters,, 2014)
In practice, managers of mergers and acquisitions (M&A) draw their attention more and more to speed of integration within their M&A strategies. In a paradoxical manner, M&A research on speed of integration is still in its infancy and remains underdeveloped. Empirical findings reach from positive over negative to non-significant relationships between speed and M&A success. Carolin Proft develops a research model which encompasses task integration speed and human integration speed as independent variables influencing the dependent variable of M&A performance. She clarifies the question of how the success factor speed can be used as a tool to enhance M&A success. Based on the data collected from 101 German speaking companies she proves that task integration speed negatively influences M&A performance while human integration speed promotes M&A success. The present study is unique as it quantitatively demonstrates that the two types of integration occur at different levels of speed. Therefore, the M&A success significantly depends on the chronology of the two types of integration.   Contents Mergers & Acquisitions – State of the Art: M&A Basic Concepts; Post-Merger Integration; Problem Statement Research Model and Hypothesis Development Methodology: Measurement Development; Sample and Data; Results Discussion: Managerial and Theoretical Implications; Limitations and Future Research    Target Groups Researchers and students in the field of International and Strategic Management, and Business Development M&A Managers, CEOs and Human Resource Managers    The Author Carolin Proft obtained her Master of Arts degree at Management Center Innsbruck, Austria. She is specialized in the field of International and Strategic Management.